Age-related differences in experienced patient-centred care among women with endometriosis. (3rd October 2022) - Strömberg, Clara; Olovsson, Matts; Grundström, Hanna
Abstract: Younger women with endometriosis report lower quality of life and seek more care. Patient-centeredness is a central part of quality of care. The aim of this study was to investigate if women younger than 35 years experience endometriosis care as less patient-centred than women 35 years and older. The ENDOCARE Questionnaire was sent to 1000 randomly selected women with verified endometriosis from 10 clinics in Sweden. Answers from 469 women were analysed using Mann–Whitney's U -test and Spearman's correlation. Our findings show that younger women experience care as less patient-centred regarding 'Physical comfort, ' 'Continuity, ' 'Access to care, ' 'Technical skills, ' and overall patient-centeredness score in comparison with older women. On the contrary, younger women experience more patient-centeredness in 'Emotional support'. Positive correlations were found for age and 'Access to care' and 'Technical skills', while a negative correlation was found for age and 'Emotional support'. Impact Statement: What is already known on this subject? There is a need for improvement of quality of endometriosis care. Patient-centeredness is an important part of care improvement work. Many factors have an impact on experienced patient-centeredness in endometriosis care, whereof age is one possible determinant. Given the impact of age on QoL and care seeking behaviour, age may also have influence on the experience patient-centeredness. What do the results of this study add? Our findings show that younger women experience their endometriosis care as less patient-centred than older women. What are the implications of these findings for clinical practice and/or further research? Our results highlight the need of improvement of endometriosis care, especially for younger women. The results contribute to the understanding of the experience of patient-centeredness, which may be used as a guidance to how healthcare recourses should be allocated. Further research is needed to identify other factors contributing to the experience of patient-centeredness. Future studies could also evaluate how different interventions can improve patient-centeredness.